Co-occurrence of depression and chronic diseases - Fryska, Zuzanna; Kuciński, Jakub; Kulik, Kacper; Matusz, Krystian; Burczyk, Rafał; Górna, Natalie; Mazurek, Ewelina; Wołejko, Adam (Journal of Education, Health and Sport, 2023)
INTRODUCTION Depression is a common and serious mood disorder mainly manifested by sadness, anhedonia, lack of hope and interest in activities once enjoyed. According to WHO depression is a leading cause of disability and inability to work worldwide. Chronic disease is every condition lasting more than 1 year and requiring medical attention. The aim of this article is to show challenges of depression and chronic diseases coexistence. DISCUSSION Depression might be a factor causing difficulties in diagnosing chronic diseases as patients are less likely to cooperate. On the other it might lead to worse compliance and higher risk of chronic diseases’ development. Studies show depression coexisting with chronic illnesses is a valid problem for public health and aggravates the course and effects of treatment of those conditions. Treating an underlying disease is as important as treating depression itself as it might lead to reduction in symptoms of depression. Moreover doctors should choose drugs having regard to depression as well as lingering conditions. SUMMARY Depression still seems to be diminished and ignored in patients with chronic illnesses even though it is proved to have a destructive influence on the health of patients. It is of high importance to raise an awareness of doctors on that subject and its scale. There are plenty of treatment methods for depression in case of chronic diseases co-occurence which gives hope for improving a quality of life of patients and achieving better effects of therapy of an underlying disease.